A DIFFERENT ANGLE ON CROSSOVER IN MUSIC - Petkov, Lyudmil (E-Journal VFU, 2024)
The topic of the article is a cycle of crossover concerts held at the Art Academy of Plovdiv. Instead of highlighting the specifics of the pedagogical and methodological work on the preparation and conduct of the musical event, the center of our attention shifts to the personality of the student performers, namely - on the impact of such events on their confidence, motivation and self-understanding. The issue is developed in the context of multiculturalism as an invariable component of today’s world and global thinking. The student performers are from the three educational levels at the Art Academy - bachelor, master, doctoral student and what unites them is the eternal striving for successful performance on the stage.